EKSKLUSIVITAS PENDIDIKAN AGAMA ISLAM DAN ANCAMAN TERHADAP TOLERANSI - Siti Maqfirah (Yayasan An-Nur Meunara Baro, 2025)
This article explores the phenomenon of exclusivity in Islamic Religious Education (IRE) in various educational institutions across Indonesia and its impact on declining tolerance within a multicultural society. The study is motivated by the growing tendency to deliver religious content in a narrow, dogmatic manner that often limits dialogue with other belief groups. Utilizing a qualitative approach through literature review and curriculum policy analysis, this research examines the content of IRE teaching materials and student attitudes toward diversity. The findings indicate that the IRE curriculum, which lacks space for inclusive and pluralistic perspectives, tends to reinforce a